Randomized studies in China show that studying and promoting civic honesty needs to consider local norms - Iris W. Hung; Yuho Yiu; Sihan Wu; Dan Liu; Liman Wang; Xiao Han (Scientific Reports)
Abstract Civic honesty is a crucial behavior that policymakers and business leaders strive to promote among citizens and employees. We conducted online and field experiments in China adapting the setting of a recent research which employed an innovative design to study civic honesty behavior around the globe. Results show that the psychological mechanism underlying lost-wallet reporting behavior in China is somewhat different from what has been suggested in the literature. Chinese participants indicated they are significantly more likely to put WeChat than email as contact information on their lost items, corroborating a local norm in China that email is infrequently used by ordinary Chinese citizens. Moreover, we tested multiple behavioral interventions in the field. Aiding a lost-property finder to connect to an owner using WeChat led to a reporting rate of 59.3% (vs. 7% as shown in a recent research that used email as the communication means; note that due to differences in experimental designs, no direct comparison of these reporting rates should be made however). Our research suggests that interacting with citizens from a targeted population to formulate locally informed research questions and design may be crucial for understanding and promoting civic honesty behavior.